The impact of enhanced sustainability outcomes on the optimal open pit to underground transition - Hall, A; Lee, D; Flanagan, M; Sharman, T; Grobler, F; Barros, N (Mine Closure 2025: Proceedings of the 18th International Conference on Mine Closure, 2025)
Sustainability considerations, including environmental, social, and governance (ESG) aspects are indeed a critical matter for the mining industry. Today, sustainability performance and credentials permeate all aspects of mineral projects, influencing everything from initial project evaluation through to operations and mine closure, and overarching corporate governance objectives. The decision to transition from open pit to underground operations is a multifaceted challenge, devoid of a one-size-fits-all solution. Traditionally, this decision hinged predominantly on economic factors such as mining costs, and technical risks; with open pit mines often perceived as offering greater certainty. However, underground mining typically encompasses many material advantages from a broader sustainability perspective, including a smaller disturbance footprint; lower greenhouse gas (GHG) emissions; greater utilisation of natural resources (better resources stewardship, less waste generation); less societal disruption; and less financial impact associated with closure. Consequently, integrating sustainability considerations into the evaluation of the optimal transition point from open pit to underground operations may expedite the transition, and lead to a smaller open pit and the earlier development of an underground mine. This paper identifies the range of mining and environmental technical factors, as well as other technological and socio-economic factors that influence the determination of the optimal transition point from open pit to underground mining – when applied in brownfield or adoption of underground mining exclusively in a greenfield project if deemed optimal. Further expanding on conventions through extensive practical experience, case studies, and advanced modelling techniques, the authors demonstrate the substantial impact that achieving superior sustainability performance outcomes has on this decision.
Keywords: sustainability